Ischemia-induced endothelial cell swelling and mitochondrial dysfunction are attenuated by cinnamtannin D1, green tea extract, and resveratrol in vitro. (October 2015) - Panickar, Kiran S.; Qin, Bolin; Anderson, Richard A.
Abstract : Polyphenols possess antioxidant and anti-inflammatory properties. Oxidative stress (OS) and inflammation have been implicated in the pathogenesis of cytotoxic brain edema in cerebral ischemia. In addition, OS and pro-inflammatory cytokines also damage the endothelial cells and the neurovascular unit. Endothelial cell swelling may contribute to a leaky blood–brain barrier which may result in vasogenic edema in the continued presence of the existing cytotoxic edema. We investigated the protective effects of polyphenols on cytotoxic cell swelling in bEND3 endothelial cultures subjected to 5 hours oxygen-glucose deprivation (OGD). A polyphenol trimer from cinnamon (cinnamtannin D1), a polyphenol-rich extract from green tea, and resveratrol prevented the OGD-induced rise in mitochondrial free radicals, cell swelling, and the dissipation of the inner mitochondrial membrane potential. Monocyte chemoattractant protein (also called CCL2), a chemokine, but not tumor necrosis factor-α or interleukin-6, augmented the cell swelling. This effect of monochemoattractant protein 1-1 was attenuated by the polyphenols. Cyclosporin A, a blocker of the mitochondrial permeability transition pore, did not attenuate cell swelling but BAPTA-AM, an intracellular calcium chelator did, indicating a role of [Ca 2+ ]i but not the mPT in cell swelling. These results indicate that the polyphenols reduce mitochondrial reactive oxygen species and subsequent cell swelling in endothelial cells following ischemic injury and thus may reduce brain edema and associated neural damage in ischemia. One possible mechanism by which the polyphenols may attenuate endothelial cell swelling is through the reduction in [Ca 2+ ]i .